PENGARUH FINANCIAL FLEXIBILITY DAN DIGITAL RISK DISCLOSURE TERHADAP NILAI PERUSAHAAN PADA SEKTOR TEKNOLOGI DI BURSA EFEK INDONESIA PERIODE 2015-2024 - Sairin Sairin (Worksheet : Jurnal Akuntansi, 2026)
This study aims to analyse the effect of financial flexibility and digital risk disclosure on firm value in the technology sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2014–2024. Financial flexibility is measured using the financial flexibility index (FFI), while digital risk disclosure is measured through content analysis of annual reports using a digital risk disclosure index (DRDI). Firm value is proxied by Tobin's Q ratio. The research sample consists of 33 technology sector companies listed on the IDX, with a total of 330 firm-year observations. The analysis method employed is multiple linear regression with panel data processed using SPSS version 26. The results showed that: (1) financial flexibility has a significant positive effect on firm value; (2) digital risk disclosure has a significant positive effect on firm value; and (3) firm size, profitability, and sales growth also positively affect firm value, while leverage negatively affects firm value. This study contributes to the accounting literature on the role of financial flexibility and transparency of digital risk information in enhancing firm value, especially in the rapidly evolving technology sector in Indonesia.